2013
DOI: 10.1155/2013/876327
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Enhances Peripheral Nerve Regeneration across Long Gaps

Abstract: This study investigated the effect of ferulic acid (FA) on peripheral nerve injury. In the in vitro test, the effect of FA on viability of Schwann cells was studied. In the in vivo test, right sciatic nerves of the rats were transected, and a 15 mm nerve defect was created. A nerve conduit made of silicone rubber tube filled with FA (5 and 25 μg/mL), or saline (control), was implanted into the nerve defect. Results show that the number of proliferating Schwann cells increased significantly in the FA-treated gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Improvement in nerve fiber arrangement could be responsible for it. Previously, Sheng-Chi Lee et al 63 advocated that FA treatment (25 μg/ml to rats) accelerates the nerve conduction velocity due to nerve regeneration and axonal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in nerve fiber arrangement could be responsible for it. Previously, Sheng-Chi Lee et al 63 advocated that FA treatment (25 μg/ml to rats) accelerates the nerve conduction velocity due to nerve regeneration and axonal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the development of several surgical techniques15, new bridging materials16171819, and therapies2021222324, the autologous nerve graft is still the “gold standard” in long peripheral nerve gap reconstruction. Although there are some disadvantages to the procedure, such as a lack of autologous nerve sources or feeling obstacles for providing area during surgery, the autologous nerve graft is closest to the normal physiological structure and function when the above-noted difficulties can be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…caffeic acid and ferulic acid are polyphenolic compounds and present in both the varieties of C. ternatea. Further, several reports indicated that caffeic acid and ferulic acid also showed neuroprotective effect [49][50][51][52][53]. Similarly, terpenoids viz.…”
Section: Tlc Finger Printingmentioning
confidence: 99%